2013
DOI: 10.1016/j.ijid.2013.06.006
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for multidrug resistance among previously treated patients with tuberculosis in eastern China: a case–control study

Abstract: Particular clinical diagnostic results, such as more than three TB foci in the lung, non-standard or irregular therapy, and adverse effects of anti-TB medication, were found to be associated with MDR-TB in previously treated TB patients. High quality directly observed treatment should be strengthened to ensure that the previously treated patients can receive standard and regular regimens.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
31
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 15 publications
1
31
0
1
Order By: Relevance
“…But gender impact on MDR/RR-TB was reported differently in different regions. There was no association with gender in several studies [8-13]. In some regions of China, studies showed that female was more likely to develop MDR/RR-TB [14, 15].…”
Section: Discussionmentioning
confidence: 99%
“…But gender impact on MDR/RR-TB was reported differently in different regions. There was no association with gender in several studies [8-13]. In some regions of China, studies showed that female was more likely to develop MDR/RR-TB [14, 15].…”
Section: Discussionmentioning
confidence: 99%
“…23 Few studies have examined risk factors for primary MDR tuberculosis and the associations that have been reported have been inconsistent. A common finding across multiple studies is that patients with MDR tuberculosis tend to be younger than those with a drug-sensitive infection, 24 with one meta-analysis reporting that patients with tuberculosis younger than 65 years were 2·5 times more likely to have MDR than those who are older than 65 years. 24 A possible explanation for this is that older patients might have tuberculosis due to activation of a latent infection acquired before the emergence of drug resistance.…”
Section: The Lancet Respiratory Medicine Commissionmentioning
confidence: 99%
“…A common finding across multiple studies is that patients with MDR tuberculosis tend to be younger than those with a drug-sensitive infection, 24 with one meta-analysis reporting that patients with tuberculosis younger than 65 years were 2·5 times more likely to have MDR than those who are older than 65 years. 24 A possible explanation for this is that older patients might have tuberculosis due to activation of a latent infection acquired before the emergence of drug resistance. Such data are consistent with findings from molecular epidemiological studies that show that younger age is a risk factor for recent transmission.…”
Section: The Lancet Respiratory Medicine Commissionmentioning
confidence: 99%
“…To the contrary, a study in other setting stated that MDR-TB was more prevalent among older age groups 20 . Moreover, regarding socio-economic factors, majority of MDR-TB patients were from low socioeconomic status 2,28,29 . This might be due to poor compliance with TB treatment often due to poor living and housing condition and limited access to medical treatment and health care services which might facilitate the spread of infectious bacilli.…”
mentioning
confidence: 99%